EL PSICODIAGNÓSTICO DE LOS PROBLEMAS DE APRENDIZAJE DESDE UN ENFOQUE MULTIMODAL - Lis Rossi, Graciela (European Scientific Journal, ESJ, 2015)
Learning problems are described with the Multimodal Model of Arnold Lazarus. Its usefulness is considered for Psychodiagnosis, affording a holistic and thorough study of all possible alterations in learning, as well as that of the individual analysis. A case study that exemplifies its importance in personality assessment, therapeutic results, and the integration of other techniques used in child psychodiagnosis was included.